The Development of Metal-Free Porous Organic Polymers for Sustainable Carbon Dioxide Photoreduction - Bariki, Ranjit (2024)
A viable tactic to effectively address the climate crisis is the production of renewable fuels via photocatalytic reactions using solar energy and available resources like carbon dioxide (CO₂) and water. Organic polymer material-based photocatalytic materials are thought to be one way to convert solar energy into valuable chemicals and other solar fuels. The use of porous organic polymers (POPs) for CO₂ fixation and capture and sequestration to produce beneficial compounds to reduce global warming is still receiving a lot of interest. Visible light-responsive organic photopolymers that are functionally designed and include a large number of heteroatoms and an extended π-conjugation allow for the generation of photogenerated charge carriers, improved absorption of visible light, increased charge separation, and decreased charge recombination during photocatalysis. Due to their rigid structure, high surface area, flexible pore size, permanent porosity, and adaptability of the backbone for the intended purpose, POPs have drawn more and more attention. These qualities have been shown to be highly advantageous for numerous sustainable applications. POPs may be broadly categorized as crystalline or amorphous according to how much long-range order they possess. In terms of performance, conducting POPs outperform inorganic semiconductors and typical organic dyes. They are light-harvesting materials with remarkable optical characteristics, photostability, cheap cost, and low cytotoxicity. Through cocatalyst loading and morphological tweaking, this review presents optimization options for POPs preparation techniques. We provide an analysis of the ways in which the preparative techniques will affect the materials’ physicochemical characteristics and, consequently, their catalytic activity. An inventory of experimental methods is provided for characterizing POPs’ optical, morphological, electrochemical, and catalytic characteristics. The focus of this review is to thoroughly investigate the photochemistry of these polymeric organic photocatalysts with an emphasis on understanding the processes of internal charge generation and transport within POPs. The review covers several types of amorphous POP materials, including those based on conjugated microporous polymers (CMPs), inherent microporosity polymers, hyper-crosslinked polymers, and porous aromatic frameworks. Additionally, common synthetic approaches for these materials are briefly discussed.